Odpowiedź :
Odpowiedź:
a)
(6²)³ : (6² * 6³) = 6^6 : 6^5 = 6^1 = 6
b)
5^-2 * (2/5)^-2 = (1/5)² * (5/2)² = 1/25 * 25/4 = 1/4
c)
(-3/8)^-2 : (-3/4)^-2 * (1/2)^-3 = (-8/3)² : (-4/3)² * 2³ = (-2³/3)² : (-2²/3)² * 2³ =
= 2^6 * 3^-2 : 2^4 : 3² * 2³ = 2² * 3^-2 : 3² * 2³ = 2^5 * 3^-4
Szczegółowe wyjaśnienie:
[tex]a)\\(6^{2})^{3}:(6^{2}\cdot6^{3}) =6^{2\cdot3}:6^{2+3} = 6^{6}:6^{5} = 6^{6-5} = 6^{1} = 6[/tex]
[tex]b)\\5^{-2}\cdot(\frac{2}{5})^{-2} = (5\cdot\frac{2}{5})^{-2} =2^{-2} = (\frac{1}{2})^{2} = \frac{1}{4}[/tex]
[tex]c)\\(-\frac{3}{8})^{-2}:(-\frac{3}{4})^{-2}\cdot(\frac{1}{2})^{-3} = (-\frac{3}{8}:(-\frac{3}{4}))^{-2}\cdot(\frac{1}{2})^{-3} =\\\\= (-\frac{3}{8}\cdot(-\frac{4}{3}))^{-2}\cdot(\frac{1}{2})^{-3} =(\frac{1}{2})^{-2}\cdot(\frac{1}{2})^{-3} = (\frac{1}{2})^{-5} = 2^{5} = 32[/tex]